Risk Analysis of Tobacco Farming At South OKU Regency South Sumatera Province - Fifian Permata Sari; Munajat Munajat (MBIA, 2019)
This study aimed to analyse the risk of tobacco farming at South OKU, South Sumatera Province. The location is determined by purposive on South OKU Regency caused it was the centre placed of tobacco farming of South Sumatera Province.. The method of this research is survey method, and simple random sampling as the sample method, with taken 25 farmers as the samples of 63 tobacco farmers in South OKU Regency. The result showed that tobacco farming in South OKU Regency, resulted in average income of Rp. 54.367.880. from these calculations it can be seen that the amount of standard deviation of Rp.15.718.548,16657. The coefficient of variation obtained is 0.2891146053 which means the CV is less than 0.5 (0.28 and L more than (22.930.783.666859 ≥ 0). This indicated that tobacco farming in South OKU Regency is protected from loss. Keywords : Risk analysis, tobacco farming, protected from loss.